Interpreting the Qur’an - Martin Nguyen (International Institute of Islamic Thought, 2007)
The book Interpreting the Qur’an is a welcome addition to the developing field of Qur’anic studies, as it contributes specifically to the study of tafsir (Qur’anic exegesis). In a field that still lacks adequate historical surveys and monographs, Saeed offers an insightful work on how the exegetical tradition can be read and understood. He attempts to plot various trajectories of development that span the classical and modern periods leading up to the present. However, the success and accuracy of his historical inquiry is largely affected by his more prominent and overarching objective: developing a modern methodology of scriptural interpretation. Over the course of twelve chapters, Saeed embarks upon an attempt to reevaluate and redefine how the Qur’an is understood. In the introduction, the author states that he is dealing only with the Qur’an’s ethico-legal concepts, the source material of Islamic jurisprudence (fiqh). Traditionally, this material has been read in a “legalistic-literalistic” fashion. However, the author hopes to replace it with a “contextualist” approach, which would take “into consideration both the socio-historical context of the Qur’an at the time of revelation in the first/seventh century and the contemporary concerns and needs of Muslims today” (p. 1) ...